Dispatching the wandering mind? Toward a laboratory method for cuing “spontaneous” off-task thought - McVay, Jennifer C.; Kane, Michael J. (Frontiers in Psychology, 2013)
Cognitive psychologists and neuroscientists study most phenomena of attention by measuring subjects’ overt responses to discrete environmental stimuli that can be manipulated to test competing theories. The mind-wandering experience, however, cannot be locally instigated by cleverly engineered stimuli. Investigators must therefore rely on correlational and observational methods to understand subjects’ flow of thought, which is only occasionally and indirectly monitored. In an effort toward changing this state of affairs, we present four experiments that develop a method for inducing mind-wandering episodes – on demand – in response to task-embedded cues. In an initial laboratory session, subjects described their personal goals and concerns across several life domains (amid some filler questionnaires). In a second session, 48 hours later, subjects completed a go/no-go task in which they responded to the perceptual features of words; unbeknownst to subjects, some stimulus words were presented in triplets to represent the personal concerns they had described in session 1. Thought probes appearing shortly after these personal-goal triplets indicated that, compared to control triplets, priming subjects’ concerns increased mind-wandering rate by about 3 – 4%. We argue that this small effect is, nonetheless, a promising development toward the pursuit of an experimentally informed, theory-driven science of mind wandering.